Laparoscopic Resection of a Hepatic Epithelioid Angiomyolipoma Revealed by Indocyanine Green Fluorescence Imaging. Issue 5 (May 2023) - Mochizuki, Kiyotaka; Aoki, Takeshi; Kusano, Tomokazu; Tomioka, Kodai; Tashiro, Yoshihiko; Koizumi, Tomotake; Matsuda, Kazuhiro; Enami, Yuta; Yamochi, Toshiko; Murakami, Masahiko
Indocyanine green fluorescence imaging (ICG-FI)—a sensitive tool for detecting tumor localization in laparoscopic surgery—produces false positive results for benign liver tumors. This report is the first case of hepatic angiomyolipoma (HAML) treated laparoscopically with ICG-FI. We present the case of a 31-year-old woman with a liver tumor that was a 13-mm mass in the anterior superior segment. Though a benign tumor was suspected, malignant potential could not be ruled out. Therefore, minimally invasive laparoscopic resection using ICG-FI was planned. ICG, intravenously injected preoperatively, revealed the tumor's existence. Pure laparoscopic hepatectomy with ICG-FI was performed for excisional biopsy, during which the tumor was resected with adequate surgical margins, followed by histological confirmation of HAML. In conclusion, it is suggested that laparoscopic resection with ICG-FI is an effective minimal invasive surgery for tumors that are difficult to detect, such as HAML, leading to a safe surgical margin.